Vibro-acoustic modeling and analysis of a coupled acoustic system comprising a partially opened cavity coupled with a flexible plate. (1st January 2018) - Shi, Shuangxia; Su, Zhu; Jin, Guoyong; Liu, Zhigang
Highlights: A general solution method is presented for the 3D coupled structural–acoustic system. Both the acoustic coupling and the structural–acoustic coupling are considered. The radiated pressure is caused by the vibration of particle and the flexible plate. The effect of cavity volume on the coupled structural–acoustic system is analyzed. The influence of the size of opening on opened cavity system is studied. Abstract: This paper is concerned with the modeling and solution method of a three-dimensional (3D) coupled acoustic system comprising a partially opened cavity coupled with a flexible plate and an exterior field of semi-infinite size, which is ubiquitously encountered in architectural acoustics and is a reasonable representation of many engineering occasions. A general solution method is presented to predict the dynamic behaviors of the three-dimensional (3D) acoustic coupled system, in which the displacement of the plate and the sound pressure in the cavity are respectively constructed in the form of the two-dimensional and three-dimensional modified Fourier series with several auxiliary functions introduced to ensure the uniform convergence of the solution over the entire solution domain. The effect of the opening is taken into account via the work done by the sound pressure acting at the coupling aperture that is contributed from the vibration of particles on the acoustic coupling interface and on the structural–acoustic coupling interface. Both the acoustic coupling between finite cavity and exterior field and the structural–acoustic coupling between flexible plate and interior acoustic field are considered in the vibro-acoustic modeling of the three-dimensional acoustic coupled acoustic system. The dynamic responses of the coupled structural–acoustic system are obtained using the Rayleigh-Ritz procedure based on the energy expressions for the coupled system. The accuracy and effectiveness of the proposed method are validated through numerical examples and comparison with results obtained by the boundary element analysis. Furthermore, the influence of the opening and the cavity volume on the acoustic behaviors of opened cavity system is studied.